High Rates of Satisfaction and Return to Dance in Current or Former Professional Ballet Dancers After Total Hip Arthroplasty With a Muscle-Sparing Direct Anterior Approach Using Custom Femoral Stems. Issue 3 (28th March 2023) - Nogier, Alexis; Tourabaly, Idriss; Ramos-Pascual, Sonia; Saffarini, Mo; Baraduc, Elodie; Barreau, Xavière; Courtin, Cyril
Background: Professional ballet dancers have high expectations after total hip arthroplasty (THA), particularly if they intend to resume dancing as performers or teachers. Purpose: To report clinical outcomes and return to dance after THA with a muscle-sparing direct anterior approach using a custom femoral stem in a cohort of current or former professional ballet dancers. Study Design: Case series; Level of evidence, 4. Methods: Twenty-three patients (26 hips) were included, that identified as current or former professional ballet dancers, from a consecutive series of 1699 hips that underwent primary THA by 1 of 2 surgeons. Both surgeons routinely implanted custom femoral stems using a muscle-sparing direct anterior approach in active and/or high-demand patients. All patients completed a questionnaire postoperatively that assessed dance capabilities, the visual analog scale (VAS) for hip pain (0-10), the VAS for satisfaction with surgery (0-10), the Oxford Hip Score (OHS), and the Forgotten Joint Score (FJS). Results: The initial cohort comprised 19 women and 4 men, with a mean age of 50.5 ± 14.9 years and a mean 38.0 ± 14.4 years of dance experience. One patient underwent revision THA for a leg-length discrepancy, leaving 22 patients (25 hips) with a mean follow-up of 3.4 ± 1.4 years. The mean VAS satisfaction score was 9.8 ± 0.6, and the mean VAS pain score was 0.5 ± 1.0. The postoperative OHS and FJS were 46 ± 2 and 92 ± 15, respectively. Overall, 16 patients resumed ballet at 5.1 ± 3.9 months, 3 resumed other types of dance, and 3 did not resume any type of dance. None of the 6 patients who did not resume ballet indicated pain in the operated hip as the reason for stopping. Conclusion: In current or former professional ballet dancers, THA by a muscle-sparing direct anterior approach using a custom femoral stem yielded excellent clinical outcomes at a minimum of 2 years, with the highest satisfaction score of 10 points reported for 88% of hips and 72% of hips being totally pain free. Furthermore, 73% of patients resumed ballet, and 86% resumed dance in general.